PARASITISME HEMIPTARSENUS VARICORNIS (GIRAULT) (HYMENOPTERA: EULOPHIDAE) TERHADAP LALAT PENGOROK DAUN LIRIOMYZA HUIDOBRENSIS (BLANCHARD) (DIPTERA: AGROMYZIDAE) PADA TANAMAN KACANG ENDUL (PHASEOLUS VULGARIS L.) DI CILOTO, JAWA BARAT - Purnomo, Aunu Rauf, Soemartono Sosromarsono, .dan Teguh Santoso (Universitas Lampung, 2003)
Parasitism of Hemiptarsenus varicornis (Girault) (Hymenoptera: Eulophidae) on leafminer fly Liriomyza huidobrensis (Blanchard) (Diptera: Agromyzidae) on kacang endul (Phaseolus vulgaris L.) in Ciloto, West Java. The objective of this research was to elucidate the relationship between leafminer and its parasitoid abundants. The research was conducted in Ciloto (Cianjur), West Java in 1999. The miner infested leaves of kacang endul were collected and placed in plastic bowls. The emerged parasitoids from those leaves were counted. The result indicated that the level of parasitism of H. varicornis during the plant growth stage ranged from 39 to 50%. The perfect density dependent between percentage parasitism and the leafminer abundance was experimentally proved.